STUDI BERBAGAI JENIS BAHAN PENGEMBANG TERHADAP REABSORPSI TEKWAN KERING IKAN GABUS - H.K, Rio Danar; Dasir, Dasir (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2017)
This study aims to determine the use of various types of developer materials to snakehead fish dry tekwan reabsorption. This study was conducted in the laboratory of the Agriculture Faculty, University of Muhammadiyah and Industrial Research and Standards, Palembang in June 2016 to August 2016. Research on the topic "The Study of Various Types of Developer Materials to Snakehead Fish Dry Tekwan Reabsorption", using a randomized block design (RAK) which were arranged in a nonfactorial with 5 (five) levels of treatment factor which repeated 4 (four) times. The parameters were observed in this study, chemical analysis includes water content and protein content on a dry tekwan, physical tests include development volume and the level of elasticity using texture analyzer. While the organoleptic tests include aroma, taste and color with preference level test which conducted on dry tekwan which already reabsorbed and already cooked. The highest water content is in T2 treatment (CaCl2 addition of 1.0% by weight of snakehead fish and tapioca flour) has an average value of 5.73%. The highest protein content was found in treatment T2 (CaCl2 addition of 1.0% by weight of snakehead fish and tapioca flour) has an average value of 17.76%. The highest development volume percentage is in T1 treatment (NaHCO3 addition of 1.0% by weight of snakehead fish and tapioca flour) has an average value of 63.77. The highest level of elasticity was found in the T0 (without the addition of developer materials/control) have an average value of 576.73 newton. The value of the highest pleasure levels of snakehead fish tekwan aroma was found in the T4 treatment (addition of instant yeast 1.0% by weight of snakehead fish and tapioca flour) with an average value of 4.25 (preferred criteria). The value of the highest pleasure levels of snakehead fish tekwan taste was found in the T4 treatment (addition of instant yeast 1.0% by weight of snakehead fish and tapioca flour) with an average value of 4.15 (preferred criteria). The value of the highest pleasure levels of snakehead fish tekwan taste was found in the T2 treatment (CaCl2 addition of 1.0% of weight of snakehead fish and tapioca flour) with an average value of 4.20 (preferred criteria).